Czas udzielania chrztu, bierzmowanie, częstość spowiedzi w diecezji augustowskiej czyli sejneńskiej i łomżyńskiej - Jemielity, Witold (Prawo Kanoniczne, 2006)
In the Catholic Church it is a religious dogma that Jesus Christ established Holy Sacraments, therefore they are constant. Whereas, practising of these sacraments by the congregation is defined by the Church common law and regional Church law, moreover, there are local and country habits added. Regulations of both kinds of law, common and regional, have changed within the centuries, what influenced the time, place and way of practising sacraments. The author showed these changes as regards the time of the child’s baptism after his birth, Confirmation and frequency of confession. In the nineteenth century the child had to be baptized until he was three days old, later it was eight days after his birth and in the midway period parents brought their children to be baptized in the period of two weeks. After the IIWW this period was much longer and reached even several months. For many centuries Confirmation seemed to be forgotten. The Bishop’s vicarious visited their Parishes and, despite being priests, they did not have the right to practise this sacrament. Considerable change as regards confirmation was introduced in the twentieth century. Sacraments of penance were associated especially with the Easter time. Numerous representants of the congregation confessed and received the Holy Communion once a year. More frequent confession and repeated receiving of the Holy Communion have become more and more popular in the several past decades.